2015
DOI: 10.1021/bi5014535
|View full text |Cite
|
Sign up to set email alerts
|

Charge and Charge-Pair Mutations Alter the Rate of Assembly and Structural Properties of Apolipoprotein C-II Amyloid Fibrils

Abstract: The misfolding, aggregation, and accumulation of proteins as amyloid fibrils is a defining characteristic of several debilitating diseases. Human apolipoprotein C-II (apoC-II) amyloid fibrils are representative of the fibrils formed by a number of plasma apolipoproteins implicated in amyloid-related disease. Previous structural analyses identified a buried charge pair between residues K30 and D69 within apoC-II amyloid fibrils. We have investigated the effects of amino acid substitutions of these residues on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 33 publications
6
31
0
Order By: Relevance
“…The solution conditions were 100 mM sodium phosphate buffer, pH 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 conditions and consistent with previous studies 19 . In contrast, a significant increase in ThT fluorescence was observed for K30D apoC-II at concentrations of 0.8, 1 and 1.5 mg/ml,indicating fibril formation proceeds at higher concentrations.…”
Section: Effect Of Apoc-ii Concentrationsupporting
confidence: 81%
See 1 more Smart Citation
“…The solution conditions were 100 mM sodium phosphate buffer, pH 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 conditions and consistent with previous studies 19 . In contrast, a significant increase in ThT fluorescence was observed for K30D apoC-II at concentrations of 0.8, 1 and 1.5 mg/ml,indicating fibril formation proceeds at higher concentrations.…”
Section: Effect Of Apoc-ii Concentrationsupporting
confidence: 81%
“…Previous studies on the role of the K30-D69 ion-pair in apoC-II fibril formation showed that a D69K mutation reduces the stability of fibrils while increasing the rate of fibril formation 19 . In contrast, a K30D mutation abolished fibril formation under standard fibril forming conditions.…”
Section: Discussionmentioning
confidence: 96%
“…show the rate of fibril formation by wild‐type apoC‐II (WT) and three apoC‐II mutants, K30D, D69K, and the double mutant K30D‐D69K (KDDK), in the absence and presence of 500 μ m 1‐Myristoyl‐2‐Hydroxy‐ sn ‐Glycero‐3‐Phosphocholine (LysoMPC). As previously reported, twisted‐ribbon fibril formation by lipid‐free WT, D69K and KDDK apoC‐II is rapid while fibril formation by K30D apoC‐II under these conditions is comparatively slow . The observed differences in the fluorescence yields of WT and mutant apoC‐II are attributable to differences in the net charge of the fibrils .…”
Section: Resultssupporting
confidence: 72%
“…As previously reported, twisted‐ribbon fibril formation by lipid‐free WT, D69K and KDDK apoC‐II is rapid while fibril formation by K30D apoC‐II under these conditions is comparatively slow . The observed differences in the fluorescence yields of WT and mutant apoC‐II are attributable to differences in the net charge of the fibrils . The rates of apoC‐II rod‐like fibril formation in the presence of 500 μ m LysoMPC differed significantly.…”
Section: Resultssupporting
confidence: 68%
“…To explore the role of the K30-D69 charge pair, we have previously studied the fibril forming ability of a D69K charge-pair mutant of apoC-II. 16 This study describes the effects of this mutation on the structural properties of apoC-II amyloid fibrils.…”
mentioning
confidence: 99%